Conserving Mangrove Forests: A Holistic Ecological and Socio-Economic Assessment of the Ariyankuppam Estuary, Puducherry - Ayyanar R; Sandeep J (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The present study is a comprehensive ecological assessment of the mangrove ecosystem in the Ariyankuppam Estuary, Puducherry, located along the southeast coast of India. This is the first integrated record of mangrove vegetation, plankton communities, and physico-chemical parameters in this estuarine environment, with additional focus on human interactions and conservation perspectives. Soil and water quality analyses revealed spatial variations in salinity, pH, dissolved oxygen, and nutrient concentrations. The mangrove flora was dominated by species such as Avicennia marina, Rhizophora mucronata, and Sonneratia alba. A total of 38 species of phytoplankton from 25 genera and 22 families were identified, with Bacillariophyceae (diatoms) comprising 63% of the total population. The most dominant phytoplankton species was Coscinodiscus granii (1.2 × 10⁶ cells/L), followed by Trichodesmium erythraeum and Oscillatoria limnosa. Zooplankton analysis revealed 24 species belonging to 14 families and 12 orders. Canonical Correspondence Analysis (CCA) showed that species distribution was strongly influenced by environmental factors such as salinity, nutrient levels, and temperature. Socio-economic data indicated moderate public awareness of mangrove importance, but limited participation in conservation efforts. The findings emphasize the need for integrated ecological management and community engagement to protect and restore the Ariyankuppam mangrove ecosystem.